Analysis Of Impact The Human Resource Management On Entrepreneur Organizations - Septian Hadi Pratama; Try Junanto; Ai Suminar; Isha Milani (OIKONOMIA: Journal of Economics and Management Science, 2023)
The human resources aspect is one of the most needed parts and also includes the needs of the community where with this human resource base a little as much as being able to develop aspects of one's own skills and potential and carry out performance processes in a business environment. Related to this, this literature review discusses human resources applied in the business sector and human resource behavior applied in organizations. This aspect of human resources is a little bit as it has begun to be applied and accepted in various industries, just like other performances. Therefore, in this literature review, it will raise aspects of human resources used in the field of business organization. This study uses a form of literature study research by applying several journals that discuss human resources in an organization, based on journal searches through several journal search sites. These journals were selected using the keyword criteria available in this study. Then, after the selection of criteria is completed. So next, it will use drawing conclusions from various journals and strengthened by theories drawn from various references. In the results of the study, several conclusions were obtained, the results of which were as follows; (1) Human resource aspects have been widely used and utilized in organizational structures. This is because with human resources, it will improve the quality of performance in the organization; (2) the influence brought by human resources is also nothing but can affect the social aspects that exist in society and become an economic driver in the business sector. Thus, this aspect of human resources is very widely applied.